2020
DOI: 10.1038/s41598-020-64930-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of peer reward and punishment for public goods problems in a localized society

Abstract: Cooperation in social dilemmas can be sustained if individuals are effectively rewarded or punished from peers within the group. However, as group size increases, we inevitably face localization, in which a global group is divided into several localized groups. in such societies, members can reward and punish only neighbors within the same localized group, while cooperation for social dilemmas should be solved through global group involvement. in this situation, the global group and the local group are not alw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Reward is typically targeted at prosocial actors, whereas punishment is more often levelled at free riders in social interactions [8][9][10]. Early research focused mainly on whether reward and punishment can increase prosocial behavior, often in laboratory experiments using social dilemma paradigms (e.g., public goods game; see Figure 1 for illustrations) [11,12], and a large-scale meta-analysis indicated that reward and punishment have similar-sized positive effects on prosocial behavior [7]. Yet, a closer examination of existing studies shows mixed evidence [10,13], suggesting that there might be boundary conditions for reward and punishment to be effective.…”
Section: Introductionmentioning
confidence: 99%
“…Reward is typically targeted at prosocial actors, whereas punishment is more often levelled at free riders in social interactions [8][9][10]. Early research focused mainly on whether reward and punishment can increase prosocial behavior, often in laboratory experiments using social dilemma paradigms (e.g., public goods game; see Figure 1 for illustrations) [11,12], and a large-scale meta-analysis indicated that reward and punishment have similar-sized positive effects on prosocial behavior [7]. Yet, a closer examination of existing studies shows mixed evidence [10,13], suggesting that there might be boundary conditions for reward and punishment to be effective.…”
Section: Introductionmentioning
confidence: 99%
“…A social dilemma refers to a situation where every individual in a group or society behaves according to her self-interest without cooperating with one another, leading to a failure of maximizing the social welfare 1 . The provisions of public goods and common pool resources are considered to be intra-and inter-generational social dilemmas, and literature finds that communication enhances cooperation, leading to Pareto improvement and socially optimal outcomes [2][3][4][5][6] . The long-run survival of humankind on Earth is claimed to depend on whether or not we can resolve intergenerational dilemmas and maintain resources by making communication and cooperation across different generations, i.e., intergenerational sustainability (IS) problems [7][8][9] .…”
mentioning
confidence: 99%
“…Both reward [16] and punishment [17] can initiate the first seed of cooperation for it to take over globally. Both are incapable of achieving global cooperation where the population is divided into localized subgroups, and the payoffs are locally inefficient [18]. There are some subtle differences also, e.g., rewarding those who reward has been shown to be preferred to punishing those who do not punish [19,20].…”
Section: Introductionmentioning
confidence: 99%